Constitucionalismo brasileiro e os desafios para a consolidação da democracia no Brasil - Fachin, Jéssica Amanda (2020)
The present paper has the goal of attaching both constitutional and social studies as a way to bring up the real possibilities of enhancing full democracy in Brazil and also to point out the barriers to its development. The research establishes the Brazilian 1988 Constitution as the result of a historic process which preserves the will of political contention through the legal system and also the democratic constitutionalism value of transforming the social reality, which are both fundamental cores of the constitutionalism. Therefore, the fact of fundamental rights not being fully enforced is presented as one of the main issues concerning the democratic absence in Brazil. Having said that, it is possible to verify an opposition between constitutional norms and social reality and grounded on dialectic-cultural theories understands the indispensable aim that the problem of constitutional norms effectiveness needs to focus not only on legal theory itself but also on politic and social matters. Considering the hybrid nature of the legal system, a close relation between constitutional law and political science is acknowledge as great importance for the comprehension of the Constitution as a whole. Thereupon, social aspects and political thoughts from the political practice of debating ideas and also from the way brazilian institutions have been historically conducted, were considered as ways to point the obstacles to enhance brazilian democracy